Analysis of amino acid variation in the P2 domain of the GII-4 norovirus VP1 protein reveals putative variant-specific epitopes. - David J Allen (PLoS ONE, 2008)
BACKGROUND: Human noroviruses are a highly diverse group of viruses classified into three of the five currently recognised Norovirus genogroups, and contain numerous genotypes or genetic clusters. Noroviruses are the major aetiological agent of endemic gastroenteritis in all age groups, as well as the cause of periodic epidemic gastroenteritis. The noroviruses most commonly associated with outbreaks of gastroenteritis are genogroup II genotype 4 (GII-4) strains. The relationship between genotypes of noroviruses with their phenotypes and antigenic profile remains poorly understood through an inability to culture these viruses and the lack of a suitable animal model. METHODOLOGY/PRINCIPAL FINDINGS: Here we describe a study of the diversity of amino acid sequences of the highly variable P2 region in the major capsid protein, VP1, of the GII-4 human noroviruses strains using sequence analysis and homology modelling techniques. CONCLUSIONS/SIGNIFICANCE: Our data identifies two sites in this region, which show significant amino acid substitutions associated with the appearance of variant strains responsible for epidemics with major public health impact. Homology modelling studies revealed the exposed nature of these sites on the capsid surface, providing supportive structural data that these two sites are likely to be associated with putative variant-specific epitopes. Furthermore, the patterns in the evolution of these viruses at these sites suggests that noroviruses follow a neutral network pattern of evolution.